Continuous traumatic stress as a mental and physical health challenge: Case studies from South Africa. (July 2018) - Kaminer, Debra; Eagle, Gillian; Crawford-Browne, Sarah
This article discusses the condition of continuous traumatic stress as common on the African continent and in other international settings characterised by very high levels of ongoing violence and threat of community, political or war-related origin. Through consideration of three case studies from South Africa, contexts of continuous traumatic stress are described, and the mental health and physical health effects of living in such contexts are elaborated. Cautions are raised about attempting to transpose existing posttraumatic stress models onto individuals exposed to situations of continuous traumatic stress, and guidelines for optimal interventions with such cases are proposed.